The life of metrical and free verse in twentieth-century poetry - Silkin, Jon (St. Martin's Press, 1997)
In a wide-ranging and compelling account of the life of metrical and free verse in the twentieth century, poet and critic Jon Silkin deepens our understanding of the way poetry works on us.